2003
DOI: 10.1097/01.sla.0000072371.95588.da
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Transfusions on Perioperative and Long-Term Outcome in Patients Following Hepatic Resection for Colorectal Metastases

Abstract: Perioperative blood transfusion is a risk factor for poor outcome after liver resection. Blood conservation methods should be used to avoid transfusion, especially in patents currently requiring limited amounts of transfused blood products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
338
1
15

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 484 publications
(367 citation statements)
references
References 64 publications
13
338
1
15
Order By: Relevance
“…[1][2][3][4][5] Despite many technical advances, intraoperative bleeding remains a problem during liver resection with 30-40% of patients receiving perioperative blood transfusions. [6][7][8] Blood transfusion carries several risks, including transfusion-transmitted viruses, transfusion-related acute lung injury, transfusion-associated circulatory overload, acute hemolytic transfusion reactions, bacterial contamination and severe allergic reactions. 9 In addition, bleeding and blood transfusion are risk factors for postoperative morbidity and in some reports, long-term cancer recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Despite many technical advances, intraoperative bleeding remains a problem during liver resection with 30-40% of patients receiving perioperative blood transfusions. [6][7][8] Blood transfusion carries several risks, including transfusion-transmitted viruses, transfusion-related acute lung injury, transfusion-associated circulatory overload, acute hemolytic transfusion reactions, bacterial contamination and severe allergic reactions. 9 In addition, bleeding and blood transfusion are risk factors for postoperative morbidity and in some reports, long-term cancer recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…15 Some investigators have even suggested that hepatectomy itself is an immunosuppressive event that results in significant Kupffer cell and T-cell dysfunction. 16,17 As such, the potential impact of perioperative complications on oncological outcomes after hepatectomy may be particularly important. Our group previously reported on the impact of perioperative complications among patients undergoing surgery for colorectal liver metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…2 During hepatic surgery, intraoperative hemorrhage is common, often necessitating blood transfusion, the latter being suggested as a predictor of postoperative outcome and poor prognosis. 3,4 Therefore, approaches to control intraoperative bleeding are presently applied worldwide and include vascular clamping methods. 5,6 However, such measures cause hepatic ischemia/reperfusion (I/R) to the liver tissue, which may contribute to postoperative liver failure.…”
mentioning
confidence: 99%